Analisis Respon Siswa MI Terhadap Model SiklusBelajar Berbasis Positive Learning Environment (Sibelpolen) Sebagai Upaya Optimalisasi Literasi Sains - Syamsi, Atikah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
In the previous stage, the author has developed the SIBELPOLEN model (positive learning environment-based learning cycle), the author has conducted several trials related to the analysis of the results of student responses to the development of this model, which in the next stage becomes the focus and purpose of this paper. The question in this research is how to analyze MI students' responses to the Sibelpolen model. This writing uses a qualitative approach, with qualitative descriptive analysis. The data processing and data analysis is done through observation sheet instruments, questionnaire sheets and interview results. In analyzing the qualitative data in this research, the authors process the data by utilizing the N-Vivo 12 Plus software, both the results of interviews, responses, learning activities, and learning outcomes of children's science literacy at the elementary school level. Sources of data were taken from students from 2 Madrasah, namely from MI PGM and MI An-Nur located in the city of Cirebon with a total of 57 children. The findings from the data showed that 88.69% of students gave a positive response regarding the Sibelpolen model in science learning. The indicator can be seen from the results of students' answers which are more systematic and varied in terms of understanding critical thinking abilities, these findings also show that students can easily strengthen their memories and provide explanations about the material that has been delivered. The implication of applying this sibelpolen model is that it can foster positive emotions in children with a positive learning approach.